Franz Liszt and His World - Gooley, Dana A. (Dana Andrew), 1969-; Gibbs, Christopher Howard (Book collections on Project MUSE., 2006)
No nineteenth-century composer had more diverse ties to his contemporary world than Franz Liszt (1811-1886). At various points in his life he made his home in Vienna, Paris, Weimar, Rome, and Budapest. In his roles as keyboard virtuoso, conductor, master teacher, and abbe, he reinvented the concert experience, advanced a progressive agenda for symphonic and dramatic music, rethought the possibilities of church music and the oratorio, and transmitted the foundations of modern pianism. The essays brought together in Franz Liszt and His World advance our understanding of the composer with fresh perspectives and an emphasis on historical contexts. Rainer Kleinertz examines Wagner's enthusiasm for the symphonic poem Orpheus; Christopher Gibbs discusses Liszt's pathbreaking Viennese concerts of 1838; Dana Gooley assesses Liszt against the backdrop of antivirtuosity polemics; Ryan Minor investigates two cantatas written in honor of Beethoven; Anna Celenza offers new insights about Liszt's experience of Italy; Susan Youens shows how Liszt's songs engage with the modernity of Heinrich Heine's poems; James Deaville looks at how publishers sustained Liszt's popularity; and Leon Botstein explores Liszt's role in the transformation of nineteenth-century preoccupations regarding religion, the nation, and art. Franz Liszt and His World also includes key biographical and critical documents from Liszt's lifetime, which open new windows on how Liszt was viewed by his contemporaries and how he wished to be viewed by posterity. Introductions to and commentaries on these documents are provided by Peter Bloom, Jose Bowen, James Deaville, Allan Keiler, Rainer Kleinertz, Ralph Locke, Rena Charnin Mueller, and Benjamin Walton.